A candidate dual AGN in a double-peaked emission-line galaxy with precessing radio jets. Issue 4 (1st December 2016) - K, Rubinur; Das, M.; Kharb, P.; Honey, M.
Abstract: We present high-resolution radio continuum observations with the Karl G. Jansky very large array at 6, 8.5, 11.5 and 15 GHz of the double-peaked emission-line galaxy 2MASXJ12032061+1319316. The radio emission has a prominent S-shaped morphology with highly symmetric radio jets that extend over a distance of ∼1.5 arcsec (1.74 kpc) on either side of the core of size ∼0.1 arcsec (116 pc). The radio jets have a helical structure resembling the precessing jets in the galaxy NGC 326 which has confirmed dual active galactic nuclei (AGN). The nuclear bulge velocity dispersion gives an upper limit of (1.56 ± 0.26) × 10 8 M⊙ for the total mass of nuclear black hole(s). We present a simple model of precessing jets in 2MASXJ1203 and find that the precession time-scale is around 10 5 yr: this matches the source lifetime estimate via spectral ageing. We find that the expected supermassive black hole (SMBH) separation corresponding to this time-scale is 0.02 pc. We used the double-peaked emission lines in 2MASXJ1203 to determine an orbital speed for a dual AGN system and the associated jet precession time-scale, which turns out to be more than the Hubble time, making it unfeasible. We conclude that the S-shaped radio jets are due to jet precession caused either by a binary/dual SMBH system, a single SMBH with a tilted accretion disc or a dual AGN system where a close pass of the secondary SMBH in the past has given rise to jet precession.